Benefits of ESG certification on commercial real estate - Collin, Gontran; Tyll, Ladislav; Balogh, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The enclosed Master Thesis provides an overview of the benefits and challenges ahead of green certification for investors. In order to identify the benefits and pitfalls of green certification in the European real estate sector in-depth interviews were conducted with ten leading investors, assessors and capital markets experts from across Europe. The interviews were written out and a thematic analytic approach was applied to the transcripts of the interviews. The findings identify that the green certified buildings obtain a higher return, thanks to the value creation by complying with green certification standards in the buildings which leads to better financing, be more appealing to tenants enabling investors to have higher rents, lower maintenance costs and higher occupancy rate which leads to higher valuations. However, this surge from investors for green certification is led by the regulatory pressure and market demand for more sustainable buildings and sustainable financial products. However, as the EU taxonomy is slowly rolling out the green certifications will have to adapt to remain relevant, while the future valuation of none certified building might be heavily affected.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses